Our Experience with Laparoscopic Appendectomy at the Department of Pediatric Surgery LRH Peshawar - Muhammad Younas Khan, Syed Asad Maroof, Fayaz Iqbal, Wardah Saleem, Muhmmand Shoaib, Kifayat (Pakistan Journal of Medical & Health Sciences, 2022)
Aim and Objective: This study aims to determine the effectiveness of laparoscopic appendectomy for children performed as emergency or emergency surgery at MTI/LRH in Peshawar, Pakistan. Material & Methods: From January 2020 to December 2022, the Department of Pediatric Surgery, Medical Teaching Institute, Lady Reading Hospital Peshawar studied acute appendicitis in children. This study comprised children with clinically confirmed acute appendicitis as indicated by blood complete, HBs Ag, HCV, ultrasound, and primary assessment. The pediatric surgical unit maintained direct resuscitation of patients’ NPO for at least 6 hours, began antibiotics, and performed laparoscopic surgery under general anesthesia. This strategy avoids additional treatment, saves time and money, reduces hospital-acquired infections and other hospital dangers, and allows for excellent local infection control without pus spreading throughout the peritoneal cavity. Laparoscopic surgery makes cholecystectomy a few-day procedure instead of a week. Laparoscopic appendectomy reduces hospital stays for children. Thus, we examined our data to determine whether children may have an emergency or same-day laparoscopic appendectomy (24-hour postoperative stay). We reviewed all three-year-olds who underwent laparoscopic appendectomy for suspected appendicitis. Results: Acute appendicitis afflicted 79 children, 4/1 male-to-female. 79 2- to 16-year-olds underwent laparoscopic appendectomy surgeries. 5% of children after laparoscopic appendectomy developed perforated appendicitis and needed an open appendectomy. Forty-one (64.5%) had severe appendicitis before surgery. 22 (27.2%) had perforated appendicitis, (5%) had ovarian cyst rupture, and 2.5% had no pathology. Surgery averaged 54 minutes. 14 of 79 primary wound closure patients had their right lower quadrant peritoneal cavity emptied. All 79 patients underwent successful appendectomy operations. Wound infection (6 patients) and stomach pain (4 patients) were the most prevalent sequelae managed conservatively. Four patients required readmission and laparotomy due to intestinal obstruction and other issues. Thirty-two children were released within 24 hours after laparoscopic appendectomy. The control group had no significant morbidity (drug rash,1: fever, 3). Practical implication: This study will provide the data on the effectiveness of the laparoscopic appendectomy for the treatment of Appendicitis. Conclusion: Our study shows that the current laparoscopic appendectomy method for treating adorable appendicitis in children is safe and may be performed as a fast-track or same-day operation with a postoperative stay of fewer than 24 hours in some children who do not have perforated appendicitis. Keywords: Laparoscopic appendectomy, Pediatric Laparoscopy, fast-track same-day surgery